Monitoring the impact of COVID-19 in Myanmar: Yangon peri-urban poultry farmers - Late July 2020 survey round - Fang, Peixun; Belton, Ben; Ei Win, Hnin; Zhang, Xiaobo (International Food Policy Research Institute, 2020)
The price of broilers continued to gradually decrease in the second half of July as supply increased – recent prices are close to the 2019 average. The skyrocketing rise in the price of broiler day-old-chicks stopped in July thanks to the Myanmar government having allowed since mid-May the importation of 3.8 million day-old-chicks. Egg prices continued to increase, growing by 14 percent from 2,300 MMK/viss in late June to 2,620 MMK/viss in late July. Cash flow is still very poor for broiler farms and worsened considerably in late July for layer farms. The PMI operational capacity indices for broiler and layer farms were much lower than those of 2019. The indices for June and July 2020 were very similar, suggesting that the operational capacity of both broiler and layer farms did not improve in July. The PMI revenue index for layer farms increased considerably in July but is still much lower than the revenue index for broiler farms. This finding suggests that COVID-19 has impacted the revenue of layer farms more significantly than the revenue of broiler farms. Supply shortages of day-old-chicks remain a bottleneck for both broiler and layer farms. Price increases for feed have become a new challenge.